Modal Budaya Guru Yoga Lokal Menghadapi Persaingan Global dalam Pariwisata Yoga di Bali - I Gede Sutarya (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
Yoga tourism in Bali has been running from the 1980s to the present day, initially created by overseas yoga teachers. In the 2000s, however, local Balinese yoga teachers began to emerge and compete with overseas yoga teachers. This article analyzes the ability of local yoga teachers to compete in the business of yoga tourism against foreign yoga teachers. The analysis focuses on the cultural capital owned by local yoga teachers and the role of that cultural capital in business competition of yoga tourism. Data was collected by literature study, non-participatory observation, in-depth interviews, and surveys. They were nalyzed by habitus theory and the product planning theory. This article concludes that the unique cultural capital possessed by Balinese yoga teachers is a provision for them to face competition in the yoga tourism business which eventually becomes a way for them to preserve that cultural capital.Keywords: yoga tourism, cultural capital, the uniqueness of Balinese yoga